Connecting spaces: the travelogues and letters of Lady Abala Bose - Mallick, Saptarshi (Abingdon, Oxon; New York, USA: Routledge, 2024)
"This book examines how nineteenth-century Bengal witnessed women writers like Krishnabhabini Devi, Prasanyamoyee Devi, Swarnakumari Devi and Abala Bose interrogated social stereotypes. It presents the first translation of travel writings and letters by Abala Bose, and examines an Indian woman's close observation as she toured India in colonial times and Europe, America and Japan at the height of British imperialism. Her travelogues in colonial India and imperial England relate to and interrogate the hegemonic role of Western ideologies and deconstruct stereotypes of women's travelogues, thus contributing to the female consciousness and tradition of women's writings. The volume will be of great interest to scholars and researchers of South Asian history, imperial and colonial history, and gender and women's studies"--
Abala Bose's travelogues -- Preface to the letters between Lady Abala Bose and Rabindranath Tagore -- Letters of Abala Bose and Rabindranath Tagore.
Includes bibliographical references and index.
Keywords: Bose, Abala, -- Lady, -- 1865-1951 -- Correspondence; Tagore, Rabindranath, -- 1861-1941 -- Correspondence; Bose, Abala, -- Lady, -- 1865-1951 -- Travel; Women -- India -- Kolkata -- Biography; Social Work; Sociology; Bengal (India) -- Social life and customs -- 20th century; Kolkata (India) -- History -- 20th century